The Power of Fatwā in Indonesia: An Analysis of MUI’s Controversial Fatwās - Mohammad Syifa Amin Widigdo; Homaidi Hamid (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2018)
This study aims to investigate socio-political factors that make certain legal opinions (fatwās) in a Muslim context become authoritative and powerful. Although these legal opinion are not binding in a principle, their supporting agents engender a degree of their efficacy and authoritativeness. They are followed and abided when external factors, either the state or society, politically or voluntarily support the implementation of those fatwās. These external factors of fatwā are largely understudied, especially in the light of how fatwā gains its authoritativeness and power to attract people to follow and comply with fatwā rulings. By studying controversial fatwās of MUI (Indonesian Ulama Council), namely on the banning of Ahmadiyyah and the prohibition of secularism, pluralism, and liberalism in religion of Islam. this article sheds a light more comprehensively on the relationship between fatwā and external factors that make this non-legal binding opinion powerful and authoritative.